A szocioökonómiai rendszerek antropológiai és etikai szemléletű megközelítése - Szabó, Balázs; Nemeskéri, Zsolt (Kultúratudományi Szemle, 2023)
In this study, we wish to formulate a critique of the economic system of our time with the help of the "toolset" of philosophy. We seek to put concepts that we consider onesided and ethically objectionable in a different light, considering, among other things, meta-anthropological and moral aspects. Our aim is not only to take the current socioeconomic system under criticism and to point out the shortcomings of the ideological background that is closely intertwined with it and considered characteristic but also to highlight the truly essential reality of man through the examiningesacralized structure.